Experience of Morphologic Left Ventricle Training in Congenitally Corrected Transposition of the Great Arteries in Children: Evaluation of the Operation Results - Stohova, Olena V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To evaluate the efficacy of morphologic left ventricle (mLV) training through pulmonary artery banding (PAB) in pediatric patients with congenitally corrected transposition of the great arteries. Materials and methods. From 2003 to 2023, 12 patients underwent PAB for mLV training at the Ukrainian Children`s Cardiac Center. The mean age of the patients was 30.3 ± 25.1 months, the mean weight was 11.6 ± 5.2 kg. Hemodynamic parameters were assessed to determine the size of the band applied to the pulmonary artery (PA) trunk during the operation. Intraoperative transesophageal echocardiography was performed in 6 patients. Transthoracic echocardiography (TTE) was performed in the early postoperative period. In the remote period, all the patients underwent TTE and X-ray angiography. Results. During PAB, the mLV pressure averaged 58 ± 12.6% (from 40% to 80%) of the systemic arterial pressure. PAB dilatation was required for one patient in the early postoperative period (postoperative day 2) because of significant hemodynamic changes. In the early postoperative period, the maximum gradient across PA measured by TTE averaged 39.3 ± 10.0 mm Hg (from 25 to 60 mm Hg). There was no hospital mortality. The follow-up period averaged 47.2 ± 26.0 months (8 to 113 months). In the long-term observation period, 2 patients (16.6%) died, one 8 months and the other 5 years after the operation. The double switch operation was performed in 6 patients, on average, 48.2 ± 6.9 months after PAB. According to angiography, the mLV pressure before the double switch operation was 90.2 ± 11.6% of that in the systemic right ventricle. The end-diastolic pressure in the mLV averaged 14 ± 4.1 mm Hg. The peak pressure gradient across the PA measured by echo was 81.3 ± 28.8 mm Hg. The mLV mass index averaged 62.9 ± 8.8 g/m2, the mLV ejection fraction averaged 61.2 ± 2.9%. Overall radiographic and echocardiographic data in these patients indicated that mLV is trained and capable of performing the role of a systemic ventricle after anatomical correction. Conclusions. PA banding as a method of mLV training can be used in patients with congenitally corrected transposition of the great arteries with intact ventricular septum, restrictive ventricular septal defects and severe tricuspid regurgitation. To evaluate the effectiveness of PAB for mLV training, a multimodal diagnostic approach is used, including non-invasive and invasive methods such as TTE, transesophageal echocardiography, and cardiac catheterization. The optimal age for PAB in patients of this group for the purpose of training the LV was on average 2-2.5 years.